Restriction endonuclease analysis of genomic DNA of isolates of Trypanosoma evansi - YADAV, S N; GHORUI, S K; RAY, D (The Indian Journal of Animal Sciences, 2014)
The present study was initiated to focus on the differences or similarities among different isolates of Trypanosoma evansi through restriction endonuclease profile. The genomic DNA of T.evansi, isolated from naturally infected buffalo, horse and camel were analysed. A panel of restriction enzymes-Alu I, Dra I, EcoR I, Hind III, Kpn I, Not I, Pst I, Sal I, Sma I and Taq I were used for complete digestion of genomic DNA. The agarose gel electrophoresis of digested DNA samples appeared as continuous smear along the electrophoretic tracks on ethidium bromide staining revealing the complex size oftrypanosome genome. There was no fixed restriction site, but in restriction enzyme Dra I and Alu I where restriction site at the region of 1.5 kb and 100 bp, respectively, appeared with background smear of DNA fragments. No heterogeneity in the nuclear DNA restriction endonuclease profile among the isolates was recorded.